2020
DOI: 10.1037/tps0000231
|View full text |Cite
|
Sign up to set email alerts
|

A higher goal during higher education: The power of purpose in life during university.

Abstract: The transition into college involves several trials and tribulations, and students' ability to deal with this process may be facilitated by finding a sense of purpose. Having a purpose has been shown to have a variety of benefits for college students, whether it is garnering the perseverance to help withstand the various stressors college students must endure or the potential it has for promoting well-being. This review describes why purpose is an important consideration for higher education researchers by not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 37 publications
2
41
0
3
Order By: Relevance
“…While purpose has previously been associated with higher relationship satisfaction (Pfund, Bono et al, 2020a), another question is whether purpose is also associated with greater stability in relationships. Past work found that purposeful people maintain greater affective stability in the midst of stressors (Hill et al, 2018), so purpose may promote this stability across a variety of relationship domains in the midst of challenges that come alongside the college transition.…”
Section: Purpose and Relationshipsmentioning
confidence: 99%
“…While purpose has previously been associated with higher relationship satisfaction (Pfund, Bono et al, 2020a), another question is whether purpose is also associated with greater stability in relationships. Past work found that purposeful people maintain greater affective stability in the midst of stressors (Hill et al, 2018), so purpose may promote this stability across a variety of relationship domains in the midst of challenges that come alongside the college transition.…”
Section: Purpose and Relationshipsmentioning
confidence: 99%
“…Regarding the nature of purposefulness, though, it may depend less on age and more on developmental context. For instance, the university years present a particularly important period for purpose formation (Pfund, Bono et al, 2020), given that students are finding what gives them a sense of purpose. Being able to predict how purposeful one will be in a given day may be more difficult during developmental periods when one is still searching for a purpose.…”
Section: Developmental Context and Discrepanciesmentioning
confidence: 99%
“…Secondly, university is the place where students are taught and trained to be ready for the next phase of life and their future. Pfund et al (2020) highlight that university life provides a unique opportunity for students to experience the "purpose development process" which consists of the process of purpose exploration and purpose commitment. In other words, the process refers to how the individual learn and explore the aspects that suitable to them and later embrace a particular way for them to shape their life goals.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…The data suggest that the majority of the students have a high level of meaning and purpose in life. Past studies show that youth with meaning and purpose in life have higher self-esteem and moral commitment (Bronk 2005;Pfund et al, 2020).…”
Section: Findings and Discussionmentioning
confidence: 99%